Komunikasi Interpersonal Petugas Pemasyarakatan dalam Pembinaan Perilaku Warga Binaan Perempuan di Bengkulu - Ary Saputra; Sri Dwi Fajarini (Jurnal MADIA (Jurnal Humas dan Media Kontemporer), 2026)
This study aims to analyse interpersonal communication in the behavioural guidance of inmates at the Class IIB Women’s Correctional Institution in Bengkulu. The study employs a qualitative method with a descriptive approach. There were six informants, comprising the Head of the Correctional Institution, the Head of the Registration and Rehabilitation Sub-Section, the Head of the Security and Order Administration Section, and three inmates. Data were collected through observation, in-depth interviews, and documentation, and were subsequently analysed using the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that interpersonal communication between correctional officers and inmates plays a crucial role in the behavioural rehabilitation process. The effectiveness of communication is demonstrated by the increased openness of inmates in disclosing their personal backgrounds and issues, the emergence of empathetic relationships between officers and inmates, the provision of support through personality development and self-reliance programmes, the development of positive attitudes among inmates towards rehabilitation activities, and the creation of communicative equality that enables inmates to express their opinions and receive feedback openly. The research findings also indicate that a communication approach which positions staff as mentors and listeners is capable of encouraging behavioural change among inmates towards a more adaptive, cooperative, and participatory approach in following the programme rehabilitation. This study contributes to the development of research on interpersonal communication within the context of the prison system by demonstrating that the dimensions of openness, empathy, supportive attitudes, positive attitudes, and equality as proposed by Joseph A. Devito are key factors in the successful rehabilitation of inmates.Keywords: interpersonal communication, behavioural rehabilitation, female prisoners, women’s correctional institutions.